2012
DOI: 10.1095/biolreprod.112.099721
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the Bull Sperm Surface Proteins That Bind Sperm to Oviductal Epithelium1

Abstract: Three Binder of SPerm proteins (BSP1, BSP3, BSP5) are secreted by bovine seminal vesicles into seminal plasma and adsorbed onto sperm. When sperm inseminated into the female reach the oviduct, the BSP proteins bind them to its epithelial lining, forming a sperm storage reservoir. Previously, we reported that binding of capacitated sperm to oviductal epithelium in vitro is lower than that of uncapacitated sperm and we proposed that reduced binding was due to loss of BSP proteins during capacitation. Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 62 publications
3
37
1
Order By: Relevance
“…Indeed, our results show a positive effect of temperature on SOD and GPX1 activity that at the same time seems to have an indirect effect on sperm quality likely to maintain a constant fitness for reproductive success ( Figure 6). Addition of SP in a range of 5-50% (v/v) to the extender minimized cryopreservation-induced membrane damage [5,9,38] or early onset of acrosome responsiveness post-thaw [16,38] due to stabilizing proteins or antioxidant enzymes in SP that provide protection to the sperm cells [6,13,31]. Results in our study indicate that addition of SP to frozen-thawed semen ameliorated the negative effects of cryopreservation compared with control sperm as reflected in higher EN as well as HOST percent values (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our results show a positive effect of temperature on SOD and GPX1 activity that at the same time seems to have an indirect effect on sperm quality likely to maintain a constant fitness for reproductive success ( Figure 6). Addition of SP in a range of 5-50% (v/v) to the extender minimized cryopreservation-induced membrane damage [5,9,38] or early onset of acrosome responsiveness post-thaw [16,38] due to stabilizing proteins or antioxidant enzymes in SP that provide protection to the sperm cells [6,13,31]. Results in our study indicate that addition of SP to frozen-thawed semen ameliorated the negative effects of cryopreservation compared with control sperm as reflected in higher EN as well as HOST percent values (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of SP may be attributed to critical components such as antioxidant enzymes and other stabilizing proteins capable of modulating sperm function [12][13][14]. However, SP is removed prior cryopreservation to dilute the semen at a specific concentration in the extender.…”
Section: Introductionmentioning
confidence: 99%
“…This binding inhibits premature capacitation and enhances the viability of spermatozoa [41,42]. Further to this, BSP1 has been shown to remain present on spermatozoa even after capacitation, suggesting a function in the binding of spermatozoa to the epithelium of the ampulla [43]. More work is required in order to know mechanisms underlying the actions performed by GBPs during sperm reservoir formation.…”
Section: Establishment Of Sperm Reservoir In Oviductmentioning
confidence: 96%
“…The exact molecular mechanism by which the reversal of these deleterious effects during cryopreservation is achieved is not fully understood. In several studies, it has been reported that SP proteins are adsorbed onto the surfaces of boar spermatozoa and that this may allow damaged spermatozoa surfaces to retain their original shape during cryopreservation [43,50].…”
Section: Cryopreservationmentioning
confidence: 99%
“…To achieve this physiological process in bovine sperm by heparin requires heparin binding to sperm and the culture media must contain HCO 3− , Ca 2+ and have a pH of 7.0 or greater for at least 4 h during in vitro incubation conditions (Bergqvist et al, 2007). Thus, heparin is considered a physiological capacitation inducer in bovine sperm and for instance a strong inducer of the acrosome reaction (Hung and Suarez, 2012). Understanding the specific role of biophysical factors is important for fertility investigations and for improving the success of assisted reproductive technologies.…”
Section: Introductionmentioning
confidence: 99%